2020
DOI: 10.1038/s41598-020-71566-x
|View full text |Cite
|
Sign up to set email alerts
|

Moderate static magnetic fields enhance antitumor CD8+ T cell function by promoting mitochondrial respiration

Abstract: With the discovery of magnetoreceptor mechanisms in animals, it materialized the novel applications of controlling cell and animal behaviors using magnetic fields. T cells have shown to be sensitive to magnetic fields. Here, we reported that exposure to moderate SMFs (static magnetic fields) led to increased granule and cytokine secretion as well as ATP production and mitochondrial respiration from CD8 + T cells. These effects were inhibited by knocking down the Uqcrb … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…Consistently, we found that mutating tax-4 could affect the SMF-dependent upregulation of three CYP genes. Moreover, recent studies on cellular effects of SMFs, together with our findings, highlight the role of mitochondria 8 , 9 , suggesting mitochondria could be an SMF sensor in the cell. Exploring the transcription factors driving the transcriptomic changes upon SMF treatment is another exciting issue to pursue.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…Consistently, we found that mutating tax-4 could affect the SMF-dependent upregulation of three CYP genes. Moreover, recent studies on cellular effects of SMFs, together with our findings, highlight the role of mitochondria 8 , 9 , suggesting mitochondria could be an SMF sensor in the cell. Exploring the transcription factors driving the transcriptomic changes upon SMF treatment is another exciting issue to pursue.…”
Section: Discussionsupporting
confidence: 79%
“…S1 ). Similarly, a recent report showed that 0.3 T SMF is more potent than 0.6 T SMF in inducing cytokine secretion of CD8 + T cells 8 . The dose-dependent feature of SMF-induced biological effects makes it intriguing to find optimal SMF treatment in the future.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…MFs can be classi ed the static magnetic elds (SMF) in various intensity ranges including week (< 1 mT), moderate (1 mT-1 T) and high (1 T <), and also electromagnetic eld (EMF) in various frequency including extremely low-frequency (< 300 Hz), intermediate (300 Hz-10 MHz) and radiofrequency (10 MHz-300 GHz) 6,7 . Moreover, pulsed EMF (PEMF) represent a sub-class of EMFs containing frequencies from 6 Hz up to 500 Hz 8,9 .…”
Section: Introductionmentioning
confidence: 99%